Effect of shear on the symmetric diblock copolymer/nanorod mixture： A dissipative particle dynamics study - 何林李 张瑞芬 季永运 (Chinese physics B, 2012)
The phase behaviours of a lamellar diblock copolymer/nanorod composite under steady shear are investigated using dissipative particle dynamics. We consider a wide range of nanorod concentrations, where the nanorods each have a preferential affinity to one of the blocks. Our results suggest that shear not only aligns the orientations of the diblock eopolymer templates and nanorods towards flow direction, but also regulates the distribution of the nanorods within the polymer matrix. Meanwhile, the shear-induced reorientation and morphology transitions of the systems also significantly depend on the nanorod concentration. At certain nanorod concentrations, the competitions between shearinduced polymer thinning and nanorods dispersion behaviours determine the phase behaviours of the composites. For high nanorod concentrations, no morphology transition is observed, but reorientation is present, in which the sheared nanorods are arranged into hexagonal packing arrays. Additionally, the orientation behaviour of nanorods is determined directly by the applied shear, also interfered with by the shear-stretched copolymer molecules.